2002
DOI: 10.1023/a:1021370111590
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: We examined the photostability of a double-stranded DNA oligomer, covalently labeled with Cy3 or Cy5 on one strand, in the presence of metallic silver island films. In our experimental configuration a minor fraction of the labeled DNA was close to the silver particles and the remainder was distant from the particles. Proximity of the fluorophores to silver island films resulted in increased intensity. Upon continuous illumination we found a fraction of the emission that was resistant to the photobleaching. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
1

Year Published

2003
2003
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 17 publications
3
53
0
1
Order By: Relevance
“…The spectra are blue shifted at larger angles (62°) and red shifted at smaller angles (56°) compared to the central angle of 59°. This shift is not due to different local environments of 2-AP but rather to the intrinsic wavelength dispersion of SPCE.In earlier studies of fluorophores near metallic particles, 23,24 we found decreases in lifetimes as compared to fluorophores distant from the particles. Hence, we examined the lifetime for 2-AP (Figure 8).…”
supporting
confidence: 50%
“…The spectra are blue shifted at larger angles (62°) and red shifted at smaller angles (56°) compared to the central angle of 59°. This shift is not due to different local environments of 2-AP but rather to the intrinsic wavelength dispersion of SPCE.In earlier studies of fluorophores near metallic particles, 23,24 we found decreases in lifetimes as compared to fluorophores distant from the particles. Hence, we examined the lifetime for 2-AP (Figure 8).…”
supporting
confidence: 50%
“…Silver nanostructures, used in recent studies for metal-enhanced fluorescence, 13,14,[17][18][19][20][21][22][23][24][25][26]29,34 show blinking that is dependent on both the type of structure studied and irradiance of the illumination source. We typically observed that silver fractal-like structures could readily be made luminescent with irradiances of 30 W/cm 2 or more, as compared to silver island films, which required at least a 3-5-fold increase, >100 W/cm 2 .…”
Section: Discussionmentioning
confidence: 99%
“…The favorable effects produced by close proximity fluorophores to metallic nanostructures includes increased quantum yields and reduced lifetimes, 13,14,17,18 increased fluorophore photostability, 13,14,19,20 enhanced multiphoton excitation, 21,22 and modified rates of energy transfer. [23][24][25] These interactions have been described as due to changes in the photonic mode density, PMD, around the fluorophore,26 and are considered to be through-space as compared to SERS, which is widely thought to be a contact interaction.27 , 28 Such effects are not normally observed in bulk media, where the photonic mode density is not that different from a vacuum, but can be changed by close proximity silver nanostructures. 26 We have recently referred to this phenomenon as radiative decay engineering (RDE), 13, 14 , 26 because we were primarily interested in changes in the radiative decay rate, which results in more detectable photons from fluorophores, but occasionally we use the term "metal-enhanced fluorescence" which additionally accounts for another favorable metal-induced effect, namely increased rates of excitation.…”
Section: Introductionmentioning
confidence: 99%
“…Under appropriate conditions proximity of fluorophores to metallic silver particles can result in increased quantum yields, increased photostability, and decreased lifetimes. Such changes are favorable for the use of fluorescence in DNA analysis [15,16] and immunoassays [17].…”
Section: Introductionmentioning
confidence: 99%